Transmission potential of African, Asian and American Zika virus strains by Aedes aegypti and Culex quinquefasciatus from Guadeloupe (French West Indies) - Lyza Hery; Antoine Boullis; Christelle Delannay; Anubis Vega-Rúa (Emerging Microbes and Infections)
Zika virus (ZIKV) is an arbovirus that has dramatically spread in South America and the Caribbean regions since 2015. The majority of vector incrimination studies available for ZIKV showed that Aedes aegypti mosquitoes are important vectors for this virus. However, several reports suggest that Culex quinquefasciatus mosquitoes may be implicated in ZIKV transmission in certain urban settings. In the present study, we evaluated the vector competence for ZIKV of Cx. quinquefasciatus and Ae. aegypti mosquitoes from Guadeloupe using African, American and Asian strains. The results demonstrated that Cx. quinquefasciatus is refractory to ZIKV infection whatever the strain tested at 7, 14 or 21 days post-infection (dpi), while ZIKV transmission was recorded in Ae. aegypti for all the three strains. The African ZIKV strain was better transmitted by Ae. aegypti (∼ 50% mean transmission efficiency) and with a shorter incubation period (7 dpi) when compared to the Asian and American strains (<14% transmission efficiency; incubation period of 14–21 dpi). Taken together, these results suggest that only Ae. aegypti mosquitoes are involved in urban ZIKV transmission in Guadeloupe and highlight a higher infectiousness of the African ZIKV strain in this mosquito species when compared to the Asian and American ones.